Kirchliche und politische Demokratie: Unterschiede und Ähnlichkeiten - Lundkvist, Sven (Kirchliche Zeitgeschichte, 1995)
This essay discusses in the first instance the question of democracy in the church. Does it exist? If so, is there a border-line between democracy in the church and in secular political affairs? How far can the church, which is tied to its confession of faith, accept the demands of the state for a democratic polity? These questions are often posed on the basis of the experience of Sweden or of Europe. But in fact, democracy in the church has to be significantly different from secular democracy, since the church's declarations of faith place a firm limit on the peoples's choices. But in its non-doctrinal aspects, there is no reason why the church cannot display democratic habits. The question, however, is how far the inner life of the church is influenced by the existence of parties and groups, whether political, religious or indifferent. In Sweden, these questions have resulted in a kind of compromise between the episcopal church and the congregational free churches, because the local parishes have already made their decisions, or are in the process of making more of their own decisions. On the other hand, it is notable that the desire to incorporate an episcopal polity seems to be growing in the congregational fellowships. The decision-making power therefore seems to be in part coming from below on the local level, but in part from above on the national level, and maybe in the future, from the international church bodies, which would mean a partial diminution of the influence of the national decision-making authorities.